2016
DOI: 10.1088/1674-1056/25/7/075202
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and structural properties of thin carbon films by very-high-frequency magnetron sputtering

Abstract: Growth and structural properties of thin a-C films prepared by the 60 MHz very-high-frequency (VHF) magnetron sputtering were investigated. The energy and flux of ions impinging the substrate were also analyzed. It is found that the thin a-C films prepared by the 60 MHz sputtering have a lower growth rate, a smooth surface, and more sp 3 contents. These features are related to the higher ion energy and the lower ions flux onto the substrate. Therefore, the 60 MHz VHF sputtering is more suitable for the prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Replacing NiO x with a new high mobility hole transporting material such as NiO@Carbon to get highly efficient regular planar heterojunction PSCs at low cost could be a promising route to fabrication via screen printing, doctor blading, and spin coating. [68] Further, the simulated investigations were focused on the effect of electrical conductivity of NiO@Carbon to provide a theoretical guideline in the performance of PSCs. Significantly, enhanced electrical conductivity, high fill factor (FF), and increased short circuit current density (J sc ) are observed in the NiO@carbon based PSCs as depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Replacing NiO x with a new high mobility hole transporting material such as NiO@Carbon to get highly efficient regular planar heterojunction PSCs at low cost could be a promising route to fabrication via screen printing, doctor blading, and spin coating. [68] Further, the simulated investigations were focused on the effect of electrical conductivity of NiO@Carbon to provide a theoretical guideline in the performance of PSCs. Significantly, enhanced electrical conductivity, high fill factor (FF), and increased short circuit current density (J sc ) are observed in the NiO@carbon based PSCs as depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the experiment, an unbalanced planar magnetron sputtering was used to deposit the Ag thin films, [26][27][28] which was driven by a 60 MHz VHF source in the power range of 50-250 W. In the cylindrical vacuum chamber, the water-cooled circular Ag target (99.999% pure, in diameter of 50 mm) was placed at the top, and the water-cooled, electrically floated stainless steel substrate holder (in diameter of 100 mm) was set at the bottom, about 70 mm away from the target surface. The sputtering target was biased with a VHF voltage of 60 MHz through a corresponding matching box.…”
Section: Methodsmentioning
confidence: 99%
“…[21][22][23][24][25] The previous works showed that the 60 MHz very-high-frequency (VHF) magnetron sputtering had a very low ions flux density and moderate ions energy. [26][27][28][29] If this VHF sputtering is used to deposit the Ag films, the initial growth of Ag films may be exactly controlled. Therefore, in this work, the initial growth and microstructure feature of Ag films prepared by the 60 MHz VHF magnetron sputtering were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the above methods, recent investigations of the plasma properties of RF and very-high-frequency (VHF) magnetron sputtering have shown that the energy and flux of ions impacting both the target and the substrate could be well adjusted by changing the driving frequency of sputtering [17,18]. Thus, the growth and structural properties of Si, C and Si 1−x C x films could be well controlled [19][20][21]. However, the effect of driving frequency on the growth and structure of Ag films is seldom reported.…”
Section: Introductionmentioning
confidence: 99%